2007
DOI: 10.2478/s11687-007-0035-3
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites of digestive tract of some teleost fish caught in the Dardanelles at Çanakkale, Turkey

Abstract: SummaryIn this study the following parasites were found in fishes from the Dardanelles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 11 publications
4
29
1
Order By: Relevance
“…According to Akmirza (2001), the parasite was more abundant in March (100%) than in August (53.3%) in T. trachurus. Values of prevalence of H. aduncum were 3.2% (adult) and 95% (larvae) in T. mediterraneus, 16.8% (adult) and 88.2% (larvae) in O. merlangus euxinus (Dimitrov, 1989), 10%-40% in Pleuronectiform fish (Gaevskaya and Solonchenko, 1997), 21.8%-54.8% in M. merlangus euxinus (İşmen and Bingel, 1999), 18% in Liza aurata (Pronkina, 2001), 84%-100% in S. sprattus phalericus (Korniychuk and Zavjalov, 2005), 15% in N. melanostomus (Özer, 2007), and 2.8%-5.6% in Apollina melanostoma (Kvach and Skora, 2007) in the Black Sea; 53%-100% in T. trachurus (Akmirza, 2001) in the Sea of Marmara; 5% in S. solea, 14.6% in P. saltatrix, 35% in L. saliens, 8% in S. aurata, and 7% in E. encrasicholus (Keser et al, 2007) in the Dardanelles; 5.88% in Scomber japonicus (Akmirza, 1997) in the Aegean Sea; and 0.5% in Mullus surmuletus (Arculeo et al, 1997) in the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Akmirza (2001), the parasite was more abundant in March (100%) than in August (53.3%) in T. trachurus. Values of prevalence of H. aduncum were 3.2% (adult) and 95% (larvae) in T. mediterraneus, 16.8% (adult) and 88.2% (larvae) in O. merlangus euxinus (Dimitrov, 1989), 10%-40% in Pleuronectiform fish (Gaevskaya and Solonchenko, 1997), 21.8%-54.8% in M. merlangus euxinus (İşmen and Bingel, 1999), 18% in Liza aurata (Pronkina, 2001), 84%-100% in S. sprattus phalericus (Korniychuk and Zavjalov, 2005), 15% in N. melanostomus (Özer, 2007), and 2.8%-5.6% in Apollina melanostoma (Kvach and Skora, 2007) in the Black Sea; 53%-100% in T. trachurus (Akmirza, 2001) in the Sea of Marmara; 5% in S. solea, 14.6% in P. saltatrix, 35% in L. saliens, 8% in S. aurata, and 7% in E. encrasicholus (Keser et al, 2007) in the Dardanelles; 5.88% in Scomber japonicus (Akmirza, 1997) in the Aegean Sea; and 0.5% in Mullus surmuletus (Arculeo et al, 1997) in the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence value of Neoechinorhynchus agilis was measured as 60% (Liza saliens) by Keser et al (2007) in the Dardanelles. It was measured as 91% (Mugil cephalus), 54% (Chelon labrosus), 32% (Liza saliens), 18% (Liza ramada), and 16% (Liza aurata) by Merella and Garippa (2001) and as 3.3% (Boops boops) by Pérez-del Olmo (2008) in the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that this species is common in scads, Trachurus spp. in the Black Sea (Korniychuk, 2005) and in T. mediterraneus in Marmara Sea (Keser et al, 2007). None of all the other digenean species previously recorded from this host in the Black Sea (Table 1) were observed during our investigation.…”
Section: Discussionmentioning
confidence: 76%
“…It was previously reported in Solea solea in the Aegean Sea by Papoutsoglou and Papaparaskeva-Papoutsoglou (1977); in Odontogadus merlangus euxinus, Spicara smaris, and Trachurus mediterraneus by Dimitrov (1989); and in Merlangius merlangus euxinus by Polyakova (2009) Progrillotia dasyatidis was reported in pleuronectiform fish from the coasts of Portugal (Marques et al, 2005). It was also found in the Sea of Marmara by Oğuz and Bray (2008 Naidenova and Mordvinova (1997) in the Mediterranean Sea; in Solea solea by Keser et al (2007) from the Dardanelles Strait; in Pleuronectes flesus by Oğuz (1989); in Anguilla anguilla by Altunel (1989) Dimitrov (1989) in the Black Sea.…”
Section: Anisocoelium Capitellatum (Rudolphi 1819) Lühe 1900mentioning
confidence: 88%
“…Recent published articles pertaining to the fish parasites from Turkey include those of İsmen and Bingel (1999), Kvach and Oğuz (2007), Oytun (1963), Özer (2007), Öztürk and Özer (2008), Sezen-Akandere (1972), Oğuz (1989Oğuz ( , 1991Oğuz ( , 1995Oğuz ( , 1996, Keser (2002), Tuncel (2003), Oğuz and Kvach (2006), Tuncel and Akmirza (2006), Keser et al (2007), and Bray (2006, 2008). There is a scarcity of articles about fish parasites from the Black Sea coasts of Turkey and there is no recorded study for the Eastern Black Sea Region of Turkey.…”
Section: Introductionmentioning
confidence: 99%